Study of Using Various Fertilizers on Four Varieties of Tomatoes (Solanum lycopersicum) - Yulianto, Asmohin; Iriany, Aniek; Sufianto (Universitas Muhammadiyah Malang, 2022)
The increasing demand for tomatoes has prompted concerns about the potential decrease in tomato supply, as reflected in rising market prices. To address this issue, efforts should be directed towards enhancing the productivity of tomato plants. This study focuses on identifying the interactive effects of fertilizer type and tomato variety on tomato plant development.Utilizing a Completely Randomized Design (CRD) with two factors, the first factor involves three types of fertilizers (Goat Manure, NPK, and Liquid Organic), while the second factor includes four tomato varieties (Permata, Donna, Serfo F1, and Tinatoon F1). Various parameters, such as plant height, number of leaves, number of branches, stem diameter, number of fruits, and fruit weight, were monitored.The study's results highlight a significant interaction between fertilizer types and tomato varieties, with the NPK fertilizer treatment and the Tinatoon F1 variety demonstrating optimal height among the tomato plants. Notably, NPK fertilizer exhibited a positive influence on tomato plant development, particularly in plant height at weeks 7, 10, and 13, as well as in the number of leaves, number of branches, fruit weight, and stem diameter. In contrast, the type of tomato plant did not significantly impact tomato growth, except for the Tinatoon Variety, which consistently outperformed others in terms of branches, leaves, stem diameter, and fruit weight during the observation period at weeks 7, 10, and 13. These findings underscore the importance of fertilizer selection, specifically favoring NPK, in optimizing tomato plant productivity.